Medical signal and imaging analysis for mucociliary clearance – ciliary beat frequency - Widiarta, Satriyoga (Nanyang Technological University, 2021)
In this paper, the Mucociliary Clearance process in the human respiratory airway is visualized using the Optical Coherence Tomography (OCT), where it focuses mainly on the rate of Ciliary Beat Frequency (CBF). Traditionally, to acquire CBF rate value in OCT images requires an observer to manually locate the cilia region and perform a time-lapse projection, however such method was considered inefficient and inaccurate.This study will be touching on an improved version in acquiring CBF value that requires lesser human intervention, it will be divided into three sections: the first section of the study involves analysis on the medical images procured through the usage of the OCT microscope to obtain a time-lapse visual of the human respiratory airway and identifying the ciliated epithelium cell using the image software called ImageJ. The second section is to automatically locate the cilia region on the OCT images. The third section is to determine the rate of the CBF in the epithelium cell by using the MATLAB software to perform a signal projection of time-lapse images procured and therefore, provided a more accurate CBF of the cilia in the respiratory system.